In situ crystallization and growth of TiO2 nanospheres between MXene layers for improved adsorption and visible light photocatalysis. Issue 11 (21st April 2021) - Zhang, Li; Ma, Pingping; Dai, Li; Li, Shijie; Yu, Wei; Guan, Jie
Abstract : In situ crystallization and growth of TiO2 nanospheres between MXene layers, which exhibited an intense adsorption capacity and improved visible light photocatalysis. Abstract : Environmental pollution has become one of the problems restricting the development of human society. The use of new materials with excellent performance to control pollution is an important solution. Transition metal carbides (MXenes) are a new class of two-dimensional materials, which have attracted great interest due to their excellent chemical and physical properties. MXene-based nanocomposites comprising multi-layered Ti3 C2 MXene (ML-Ti3 C2 ) nanosheets and titanium dioxide (TiO2 ) were fabricated via vapor phase hydrolysis in this work. TiO2 nanospheres crystallized and in situ grew between the MXene layers, which stretched the MXene sheet to form a multi-layer MXene sheet with swelling space. The equilibrium adsorption capacity of methylene blue (MB) demonstrates that the TiO2 /ML-Ti3 C2 nanocomposites have a high adsorption capacity for dye molecules (149.47 mg g −1, 40 min), which is in line with the second-order kinetic model and the Langmuir isotherm model. A high-concentration MB solution of 150 mg L −1 could be completely degraded under visible light irradiation within 4 h. The improved photocatalytic efficiency of the nanocomposites could be ascribed to the synergy of adsorption and photocatalysis, since the ML-Ti3 C2 MXene can intensely adsorb polar or non-polar organic pollutants which improves the mass transfer efficiency, while the heterojunction formed between the ML-Ti3 C2 MXene and TiO2 nanospheres prolongs the photogenerated carrier lifetime of the composite photocatalyst. This work reveals that the instability of Ti3 C2 will not reduce the decontamination ability of composite materials. This work also provides new evidence for the design and modification of MXene-based nanocomposites for environmental restoration.